2006
DOI: 10.1177/154405910608501005
|View full text |Cite
|
Sign up to set email alerts
|

Eugenol Inhibits Sodium Currents in Dental Afferent Neurons

Abstract: Although eugenol is widely used in dentistry, little is known about the molecular mechanisms responsible for its anesthetic properties. In addition to calcium channels, recently demonstrated by our group, there could be another molecular target for eugenol. Using a whole-cell patch-clamp technique, we investigated the effect of eugenol on voltage-gated sodium channel currents ( I Na) in rat dental primary afferent neurons identified by retrograde labeling with a fluorescent dye in maxillary molars. Eugenol inh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
63
1
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(70 citation statements)
references
References 21 publications
2
63
1
4
Order By: Relevance
“…El efecto anestésico y analgésico del eugenol ha sido atribuido a su acción inhibitoria sobre los canales de sodio (Park et al, 2006) y calcio, especialmente los canales tipo N-calcio o High voltage activated calcium channel (HVACC), dado que bloquea la generación del potencial de acción y produce una disminución en la liberación de neurotransmisores dependientes de calcio en las terminaciones presinápticas neuronales (Lee et al, 2005). Estudios in vitro han demostrado el efecto bloqueante del eugenol sobre los receptores vaniloides (TRPV1-Transient receptor potential vanilloid 1), inhibiendo así la transmisión del dolor (Yang et al, 2003); sin embargo, Lee et al (2005) indican que la acción del eugenol no es dependiente de TRPV1.…”
Section: Discussionunclassified
“…El efecto anestésico y analgésico del eugenol ha sido atribuido a su acción inhibitoria sobre los canales de sodio (Park et al, 2006) y calcio, especialmente los canales tipo N-calcio o High voltage activated calcium channel (HVACC), dado que bloquea la generación del potencial de acción y produce una disminución en la liberación de neurotransmisores dependientes de calcio en las terminaciones presinápticas neuronales (Lee et al, 2005). Estudios in vitro han demostrado el efecto bloqueante del eugenol sobre los receptores vaniloides (TRPV1-Transient receptor potential vanilloid 1), inhibiendo así la transmisión del dolor (Yang et al, 2003); sin embargo, Lee et al (2005) indican que la acción del eugenol no es dependiente de TRPV1.…”
Section: Discussionunclassified
“…[11][12][13] In addition to this, it is evident that both the calcium and sodium channels are involved in overall regulation of cellular and neuronal excitability. 14 Whether the same mechanism accounts for its other CNS effects still remains obscure.…”
Section: Introductionmentioning
confidence: 99%
“…Eugenol has been reported to inhibit multiple ion channels detected in TG neurons as follows: the IC 50 values for voltage-activated Na 1 channels, HVA Ca 21 channels, voltage-activated K 1 channels, and hyperpolarization-activated cation channels are ∼600 mM, 1 mM, 376 mM, and 157 mM, respectively (Lee et al, 2005;Park et al, 2006Park et al, , 2009Li et al, 2007;Yeon et al, 2011). Taken together with the previous findings, we suggest that T-type channels are additional molecular targets for eugenol and therefore are likely to play a part in eugenol's underlying mechanism of analgesia.…”
Section: Discussionmentioning
confidence: 99%
“…Extensive studies to unveil the painrelieving mechanism of eugenol have found that the chemical potently inhibits diverse ion channels expressed in trigeminal ganglion (TG) neurons that sense dental pain (Lee et al, 2005;Park et al, 2006;Kim et al, 2011). In particular, voltageactivated Na 1 channels and high voltage-activated (HVA) Ca 21 channels have been implicated as eugenol's molecular targets for lessening pain (Lee et al, 2005;Park et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation